NAFAS eCitra Exhibition 2025. - Auzani Zeda, Mohamed Kassim (2025)
NaFas is a lyrical abstract animation. The work emerges from my ongoing exploration of light projections and their ability to carry stories across surfaces. This piece draws its breath from today’s global flotillas that set sail toward G with aid and hope. Here, technology and narrative intersect to remind us that humanity's voyage is ongoing: from shore to shore, generation to generation, a continuity of endurance and compassion. NaFas seeks to gesture toward the unseen strength within it, where the resilience of those who set sail against all odds and the enduring dream of freedom meet.